1998
DOI: 10.1002/(sici)1521-4141(199802)28:02<625::aid-immu625>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Differential processing of influenza nucleoprotein in human and mouse cells

Abstract: To investigate how early events in antigen processing affect the repertoire of peptides presented by MHC class I molecules, we compared the presentation of the influenza A nucleoprotein epitope 265-273 by HLA-A3 class I molecules in human and mouse cells. Mouse cells that express HLA-A3 failed to present the NP265-273 peptide when contained within the full-length nucleoprotein, to HLA-A3-restricted human cytotoxic T lymphocytes. However, when the epitope was generated directly in the cytosol using a recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 50 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Species-specific generation of peptide epitopes may preclude E7/A2/1 and E7/A2/2 peptides in mice; indeed this phenomenon has been implicated as an explanation of differential presentation of a HLA-A3 antigenic epitope from influenza A nucleoprotein by mouse and human cells. 36 However, if the HLA A*0201 E7 peptides were generated, selective impaired peptide translocation into the endoplasmic reticulum lumen by murine transporter associated with antigen processing (TAP) could possibly preclude epitope presentation. Alternatively, any of the multiple molecular interactions which collaborate to load peptides efficiently into the antigen-binding cleft of the class 1 molecules, including association of empty class 1/b 2 -microglobulin complexes with calnexin, calreticulin and ER-60 chaperones, 37-39 may be sub-optimal in the case of E7 HLA A*0201 peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Species-specific generation of peptide epitopes may preclude E7/A2/1 and E7/A2/2 peptides in mice; indeed this phenomenon has been implicated as an explanation of differential presentation of a HLA-A3 antigenic epitope from influenza A nucleoprotein by mouse and human cells. 36 However, if the HLA A*0201 E7 peptides were generated, selective impaired peptide translocation into the endoplasmic reticulum lumen by murine transporter associated with antigen processing (TAP) could possibly preclude epitope presentation. Alternatively, any of the multiple molecular interactions which collaborate to load peptides efficiently into the antigen-binding cleft of the class 1 molecules, including association of empty class 1/b 2 -microglobulin complexes with calnexin, calreticulin and ER-60 chaperones, 37-39 may be sub-optimal in the case of E7 HLA A*0201 peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to HAP1 cells with TAP-deficiency, cells with knockout of TSN displayed slightly reduced amounts of total MHC-I surface molecules, while A*02:01 surface molecules were substantially decreased and B*40:01 surface molecules were increased. This indicates that TAP- and TSN-deficiency diversely affects the surface expression of varying MHC-I allomorphs and provides an explanation for contrasting observations in mouse and human cells ( 21 , 50 , 56 ), in addition to species-dependent characteristics of TAP, TSN, and the immunoproteasome ( 57 59 ). Upon separate expression, A*02:01 and B*40:01 are TSN-independent, as previously reported ( 60 ).…”
Section: Discussionmentioning
confidence: 82%
“…TAP complex (shaped by TAP1 and TAP2 subunits) is a necessary transporter for translocating peptides, which were obtained via proteasome degradation, from the cytosol to ER, where HLA class I assembly takes place. Previous studies have demonstrated that in mice and humans, the TAP complex can play a crucial role in the translocation of viral epitopes to ER [36,37], and mutations in TAP1 or TAP2 result in structural changes that can alter antigen recognition and presentation. In this sense, SNPs in TAP2 have been previously associated with a higher risk for ankylosing spondylitis [22] and cervical carcinoma associated with HPV [24].…”
Section: Discussionmentioning
confidence: 99%